Overexpression of transcriptional regulator and tailoring enzyme leads to the discovery of anti-inflammatory meroterpenoids from marine-derived fungus Alternaria alternata JJY-32 - Liu, Guowei; Liu, Dan; Li, Zongyuan; Jiao, Jieying; Hou, Xuewen; Zhang, Xiaomin; Che, Qian; Zhu, Tianjiao; Li, Dehai; Zhang, Guojian (Frontiers in Marine Science, 2022)
Four new ACTG-toxins like meroterpenoids tricycloalternarenes O-R were discovered from a marine-derived fungus Alternaria alternata JJY-32 by the overexpression of a LaeA-like global transcriptional regulator and a MpaB-like biosynthetic tailoring enzyme. Among those structures, tricycloalternarene O possesses a non-canonical cyclohexanone-pyran fused furan ring structure and tricycloalternarene R contains a truncated isoprenoid terminal. The structures were elucidated based on comprehensive 1D and 2D NMR data and assisted by ECD calculations. Tricycloalternarenes O-R showed potent anti-inflammatory activity in TLR4-transfected microphage cells (RAW264.7).